2020
DOI: 10.1097/md.0000000000022014
|View full text |Cite
|
Sign up to set email alerts
|

The association of Th17/Treg cells expression in peripheral blood and chronic spontaneous urticaria

Abstract: Background: The pathogenesis of chronic spontaneous urticaria (CSU) is not clear, but its occurrence is closely related to the immune state of the body, that is, the balance of T cell subsets. Previous studies have confirmed that the dynamic imbalance of Th1/Th2 cells in CD4+T cell subsets of T cell subsets is closely related to the pathogenesis of CSU, but there are few studies on the relationship between the dynamic imbalance of Th17/Treg cells in CD4+T cell subsets and the pathogenesis of CSU. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 9 publications
2
4
0
Order By: Relevance
“…Conversely, Treg cells exhibited a significant negative correlation pruritus level, disease severity, and quality of life in CSU patients. These results suggest that the dysregulation of Th17/Treg in peripheral blood may contribute to the pathogenesis of CSU 38 . Similar associations between Th17/Treg cells and disease severity has been reported in other skin diseases, such as atopic dermatitis, where the ratio of Th17 cells is positively associated with disease severity, while the proportion of Treg cells is inversely correlated 39 .…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Conversely, Treg cells exhibited a significant negative correlation pruritus level, disease severity, and quality of life in CSU patients. These results suggest that the dysregulation of Th17/Treg in peripheral blood may contribute to the pathogenesis of CSU 38 . Similar associations between Th17/Treg cells and disease severity has been reported in other skin diseases, such as atopic dermatitis, where the ratio of Th17 cells is positively associated with disease severity, while the proportion of Treg cells is inversely correlated 39 .…”
Section: Discussionsupporting
confidence: 82%
“…These results suggest that the dysregulation of Th17/Treg in peripheral blood may contribute to the pathogenesis of CSU. 38 Similar associations between Th17/Treg cells and disease severity has been reported in other skin diseases, such as atopic dermatitis, where the ratio of Th17 cells is positively associated with disease severity, while the proportion of Treg cells is inversely correlated. 39 In psoriasis, the absence of Treg cells has been shown to contribute the disease maintenance and exacerbation.…”
Section: Discussionsupporting
confidence: 65%
“…We found decreased levels of mRNA for FOXP3 and IL10 genes. Earlier it was shown that circulating FOXP3+ Tregs are reduced and/or defective under CU [35]. Arshi and colleagues (2014) demonstrated a significant reduction of circulating CD4 + CD25 + FOXP3 + T cells in patients with CU compared to control individuals [36].…”
Section: Discussionmentioning
confidence: 99%
“…Chen et al found that the Th1 and Th17 cytokines in plasma were significantly increased in CSU 24 . The meta‐analysis by Yu et al suggested that the imbalance of Th17/Treg cells in peripheral blood is involved in the pathogenesis of CSU 27 . These results imply that Th17 cells and IL‐17 may play a role in the pathogenesis of CSU, which, however, remains to be further studied due to limited evidence.…”
Section: Discussionmentioning
confidence: 99%